Artikel Etika Deontologi sebagai Model dalam Penerapannya pada Profesi Keperawatan - Rorah, Ignatius Rolly Coun; Mangundap, Jelvi Monica; Loho, Ambrosius Markus (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The ethics of the nursing profession is the main point that must be pursued by a nurse. The ethics of the nursing profession is important because it is something that nurses encounter all the time when they work in a health environment. From this simple fact, ethics also needs to be strictly understood because of the breadth of ethical theories that exist. Ethics is a science that seeks orientation, in the context of the nursing profession, ethics becomes a critical evaluation of every action of a nurse. Likewise, a nurse must have a professional attitude. In the context of writing this article, deontological ethics will be a model for applying ethics to the nursing profession. Deontological ethics emphasizes moral obligations, which cannot but be the primary choice, which must be carried out for the purpose of that obligation. Action based on obligation is not merely for the purpose of happiness. A morality must be truly autonomous / independent and centered on the human subject. In that framework, every nurse needs to understand that her actions cannot be since the patient needs this kind of treatment, then she carries out or executes it, but beyond that, the nurse must carry out treatment based on the understanding that the actions she takes are her moral obligations towards others (patients).